De lo multicultural a lo interdisciplinario o cómo opera la ciencia ficción de Marcelo Cohen - Ricardo Torre (Cuadernos LIRICO)
If in the eighties and nineties, Marcelo Cohen’s narrative work has the particularity of presenting multicultural scenarios, a mixture of cultures (Insomnio, 1985; El oído absoluto, 1989; El testamento de O’Jaral, 1995, just to cite three of his best-known novels), from the twenty-first century onwards the corpus constituted by his literary production is tinged with nuances that could be described as "interdisciplinary". We propose to explore this interdisciplinarity of the cohenian work, in the sense that it recovers and exploits the concerns of various social and human sciences as well as artistic disciplines.